The Relationship between Nutritional Status and Physical Fitness in Pilot International Standard School (RSBI) at the Level of Junior High School in Padang - Deri Putra; Nurlan Kusmaedi; Amung Mamun; Syafrudin (Institute of Medico-legal Publications Pvt Ltd, 2021)
The problem of this research is the low of level of physical fitness of students of Pilot International StandardSchool (SMP level) in Padang. It happened because of lack of nutrional status and physical activity.The purpose of this research is to reveal the correlation between nutrional status and physical activity,individually and in group. This research is Quantitative Reaearch that used correlational technique continuedby counting the contribution of independent variables to dependent variables. The accessible population ofthis research was all male students (448) of RSBI school in Padang, academic year 2011/2012. The sampleof this research was 67 students or 15% of accessible population by using proportional technique of randomsampling. The instrument of this research to measure physical fitness (Y) was Multistage Running Test(Tes MRT) ; Nutrional Status (X1) with the measure of weight and age converted to Classification Tableof Society Nutritional Status, Directorate of Community Nutrition, Department of Health of Republic ofIndonesia 1999 ; and Psysical Activity (X2) with questionaire. The results of the research are: (1).Thereis a significant relationship between nutrional status and physical fitness and contributed for 12.00% . (2).There is a significant relationship between physical activity and physical fitness and contributed for 26.00%.(3). There is a significant relationship between nutritional status and physical activity and contributed for29.00%. Thus, it can be concluded that increasing the psysical fitness of RSBI students in Padang can bedone by increasing Nutrional Status and Psysical Activity individually and in group.